Field Investigation of Factors Affecting Skid Resistance Variations in Asphalt Pavements - Christina Plati; Konstantina Georgouli (The Baltic Journal of Road and Bridge Engineering)
Pavement management activities consist mainly of three sequential yet interconnected processes: condition assessment, performance prediction and needs analysis. On this basis, knowledge of the evolution of skid resistance over time is important for pavement maintenance/rehabilitation planning. Seasonal and long term variations have a significant effect on skid resistance evolution. In the present study this effect is thoroughly investigated by modelling field data to provide a structure for the evolution of skid resistance in asphalt pavements. The considered field data includes the results of skid resistance measurements that were performed along 29 highways pavement sections of similar asphalt mix properties, with a fixed slip system (Grip Tester), over a period of four years and during different seasons. The developed model addresses that skid resistance is strongly related to the past level of surface friction, traffic, temperature and precipitation. The model was verified with a high degree of statistical certainty ensuring that mistakes have not been made in implementing the model. Furthermore, it was validated as its predictions have matched additional experimental data, with high precision (95% confidence level). This result produces evidence in support of the statement that the developed model provides accurate information about the variations of skid resistance in asphalt pavements.